Metabolites of TB-500 peptide in various in-vitro enzyme systems by UHPLC-MS/MS - RAHAMAN KHANDOKER ASIQUR; Muresan Anca Raluca; FARZANA BINTE RAFIQUE; Ki Hun Kim; Lee Kang Mi; Hophil Min; Kim Ho Jun; Changmin Sung; SON Junghyun; Lee Jae Ick; Kwon, Oh-Seung (Proceedings of the 38th Cologne Workshop, 2020)
TB-500 is a preparation of seven peptides prepared from the active site of thymosin β4. Thymosin β4 has effects on tissue regeneration, anti-inflammation, and fast repair capabilities with potential of abuse in athletes. TB-500 misuse was found in equine sports, and is known to be used illegally in athletes. In this study, we aimed to find out new metabolites of TB-500 peptide in various in-vitro enzyme systems such as human kidney microsome, rat liver microsome, rat liver cytosol, rat liver S9, human serum, and human skin S9. The metabolic reaction was conducted after prolonged incubation (22 hr) with various enzymes and the metabolites were analyzed in a full-scan mode by liquid chromatography coupled with MS/MS (Q-Exactive). As the results, human kidney microsome and rat liver microsome systems showed higher concentration of metabolites than the rest of enzymes. We found N-acetylleucine (Acetyl-Leu-OH; m/z 174) as a new metabolite. The new metabolite, N-acetylleucine (Acetyl-Leu-OH; m/z 174), was also found in all enzyme systems used. The other metabolites such as acetyl-Leu-Lys-Lys-Thr-Glu (m/z 660), acetyl-Leu-Lys (m/z 302), and acetyl-Leu-Lys-Lys (m/z 430) were detected. We suggest that human kidney microsome or rat liver microsome systems is better enzyme systems for TB-500 metabolism studies than cytosol, S9 and serum. We report for the first time N-acetylleucine as a metabolite of TB-500. Therefore, N-acetylleucine detection in serum and urine also can be a useful marker of detecting TB-500 abuse in doping.
Keywords: TB 500; null; Metabolites; null; HHPLC-Ms/MS